Changes in postural control in patients with Parkinson's disease: a posturographic study. Issue 3 (September 2016) - Doná, F.; Aquino, C.C.; Gazzola, J.M.; Borges, V.; Silva, S.M.C.A.; Ganança, F.F.; Caovilla, H.H.; Ferraz, H.B.
Abstract: Objectives: Postural instability is one of the most disabling features in Parkinson's disease (PD), and often leads to falls that reduce mobility and functional capacity. The objectives of this study were to analyse the limit of stability (LOS) and influence of the manipulation of visual, somatosensorial and visual–vestibular information on postural control in patients with PD and healthy subjects. Design: Cross-sectional. Setting: Movement Disorders Unit, university setting. Participants: Eighty-two subjects aged between 37 and 83 years: 41 with Parkinson's disease in the 'on' state and 41 healthy subjects with no neurological disorders. Both groups were matched in terms of sex and age. Main outcome measures: Unified Parkinson's Disease Rating Scale (UPDRS)–motor score, modified Hoehn and Yahr staging, Dynamic Gait Index (DGI) and posturography with integrated virtual reality. The parameters analysed by posturography were LOS area, area of body centre of pressure excursion and balance functional reserve in the standing position in 10 conditions (open and closed eyes, unstable surface with eyes closed, saccadic and optokinetic stimuli, and visual–vestibular interaction). Results: The mean UPDRS motor score and DGI score were 27 [standard deviation (SD) 14] and 21 (SD 3), respectively. Thirteen participants scored between 0 and 19 points, indicating major risk of falls. Posturographic assessment showed that patients with PD had significantly lower LOS area and balance functional reserve values, and greater body sway area in all posturographic conditions compared with healthy subjects. Conclusions: Patients with PD have reduced LOS area and greater postural sway compared with healthy subjects. The deterioration in postural control was significantly associated with major risk of falls.